The dichotomy of melville’s Moby Dick: American transcendentalism and anti-transcendentalism - Yalçın, Olgahan Bakşi (Atatürk Üniversitesi, 2019)
Counting on his own experiences as a seaman aboard whaling ships, American novelist Herman Melville (1819─1891) comments on the complex human relationship with the sea and its uncertainties in his masterpiece, Moby Dick (1851). To this end, in his maritime novel, Melville tells the story of the obsessive quest of Captain Ahab of the whaler Pequod for revenge on Moby Dick, the albino sperm whale that destroyed his vessel and bit off his leg at the knee on the previous whaling voyage. In creating a character like Ahab, Melville seems to emphasize the evil and destructive side of humanity, focusing on the limitations and potential destructiveness of human nature. On the other hand, the narrator of the novel, Ishmael, displays many aspects of American transcendentalism throughout the novel. Thus, the two opposite protagonists are reflected in the structure of the novel as the transcendental idealism and optimism that Ishmael displays in the early part of the novel are replaced by Ahab’s obsession for revenge and dictatorial leadership in the second half of the book, which is also appropriate for Shakespearean tragedy. This paper seeks to explore how the characters of Ishmael and Captain Ahab in Moby Dick match American transcendental idealism with dark romanticism in the form of a Shakespearean tragic plot. Balina gemilerinde denizcilik yaparken edindiği deneyimlerden yola çıkan Amerikalı romancı Herman Melville (1819─1891), Moby Dick (1851) isimli başyapıtında insanın denizle ve denizin belirsizlikleri ile olan karmaşık ilişkisini ele alır. Bu amaçla, denizcilik temalı romanında Melville, balina avcısı Kaptan Ahab’ın, bir önceki av sırasında gemisini tahrip eden ve bacağını dizinden koparan albino sperm balinası Moby Dick’ten intikamını almak için girdiği saplantılı arayışının hikâyesini anlatıyor. Ahab gibi bir karakter yaratırken, Melville, insan doğasının kötü, yıkıcı yanını ele almakta ve insan doğasının sınırlılığı ile potansiyel yıkıcılığına odaklanmaktadır. Öte yandan, romanın anlatıcısı Ishmael, roman ...